Progress in rechargeable aqueous zinc‐ and aluminum‐ion battery electrodes : challenges and outlook - Verma, Vivek (2020)
Modern cities demand a reliable supply of electricity when and where it is needed, therefore a key design for power generators feeding on noncontinuous, nonfuel renewables is installing auxiliary battery‐type energy storage systems (BESS). Batteries using Zn ions or Al ions in aqueous electrolytes are highly attractive due to low cost and elemental abundance considerations, but attaining reversibility at a high energy density and long‐life operation is challenging. Here, the authors review recent reports of reversible aqueous‐electrolyte batteries, focusing on how mechanisms of electrochemical activation, insertion, and conversion occur. Further, key issues related to cation mobility, electrode stability, the formation of electrode–electrolyte interface, and electrolyte decomposition, along with possible solutions or research directions for enabling superior performance of aqueous Zn‐ion batteries and Al‐ion batteries are explored.